Impulse Buying in Fashion Retail: Evidence at the Department Store in Daerah Istimewa Yogyakarta - Saptaningsih Sumarmi; Puspa Ayu Prasyanti (Jurnal Ilmiah Manajemen dan Bisnis, 2021)
Abstract: This study aims to examine shopping lifestyle, fashion involvement, store atmosphere as an antecedent of impulse buying behavior. The research population has made repeat purchases at the Matahari Department Store Malioboro Mall, Yogyakarta. The sampling method uses purposive sampling, with a total sample of 115 respondents. The data analysis method uses Descriptive Analysis and Multiple Linear Regression Analysis. The results found that shopping lifestyle, fashion involvement, store atmosphere partially or simultaneously affect impulse buying behaviorKeywords: shopping lifestyle, fashion involvement, store atmosphere, impulse buying behavior